ChemInform Abstract: A Copper‐Based Metal—Organic Framework Acts as a Bifunctional Catalyst for the Homocoupling of Arylboronic Acids and Epoxidation of Olefins. Issue 27 (16th June 2016) - Parshamoni, Srinivasulu; Telangae, Jyothi; Sanda, Suresh; Konar, Sanjit
Abstract: Biaryls are prepared by the homocoupling of arylboronic acids and epoxides are obtained by epoxidation of olefins under mild conditions using a Cu2 Br2 ‐based metal—organic framework as catalyst.